Nowe instrumenty ekonomiczne ochrony środowiska jako wyzwanie dla rachunkowości i sprawozdawczości przedsiębiorstw - Sidorczuk-Pietraszko, Edyta (New economic instruments in environmental protection - a challenge for enterprises' financial reporting, 2007)
New instruments of environmental policy being introduced in environment management system in Poland reąuire accounting standardized approaches towards recognition, valuation and disclosure of transactions resulting from their functioning. These transactions are disclosed in books and financial statements of companies within the existing accounting framework. However, due to increasing environmental costs of companies, significance of information related to environmental impact and stakeholders having interest in these issues, comprehensive disclosure of environment-related information becomes morę and morę important. The paper describes the issues related to recognition and accounting disclosure of transactions resulting from regulations on emission trading system and on waste electrical and electronic eąuipment, which were introduced in Poland in 2005.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 495-506